2023
DOI: 10.1021/acs.nanolett.2c03682
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticle-Incorporated Mesenchymal Stem Cells for Alzheimer’s Disease Treatment

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease with multifactorial pathogenesis. However, most current therapeutic approaches for AD target a single pathophysiological mechanism, generally resulting in unsatisfactory therapeutic outcomes. Recently, mesenchymal stem cell (MSC) therapy, which targets multiple pathological mechanisms of AD, has been explored as a novel treatment. However, the low brain retention efficiency of administered MSCs limits their therapeutic efficacy. In addition, autologous MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Various MNPs have been considered for the carriers of chemotherapeutic drugs due to their advantages of enhanced bioavailability, minimal side effects, appropriate degradation, and targeted delivery [ [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] ]. Ferroptosis-induction cancer nanomedicines utilizing MNPs have been produced and tested, a summary of which is provided in Table 2 .…”
Section: Ferroptosis Inducers For Ferroptosis Cancer Therapymentioning
confidence: 99%
“…Various MNPs have been considered for the carriers of chemotherapeutic drugs due to their advantages of enhanced bioavailability, minimal side effects, appropriate degradation, and targeted delivery [ [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] ]. Ferroptosis-induction cancer nanomedicines utilizing MNPs have been produced and tested, a summary of which is provided in Table 2 .…”
Section: Ferroptosis Inducers For Ferroptosis Cancer Therapymentioning
confidence: 99%
“…Reproduced from Ref. [118] with permission. (B) Illustration of neural stem cell (NSC) differentiation pathways in AD mice induced by chiral nanoparticles (NPs) under 808 nm NIR laser irradiation.…”
Section: Nanomedicines For Stem Cell Therapymentioning
confidence: 99%
“…In addition, IONP‐loaded MSCs acquire magnetic properties and can be enriched in the brain parenchyma under an external magnetic field, reducing adverse effects caused by off‐target activity (Figure 7A). [118] In addition, MSCs and other exogenous stem cells (mainly pluripotent stem cells and neuronal stem cells [197] ) can be transformed into highly differentiated somatic cells. Traditionally, the differentiation behavior of stem cells is regulated by environmental factors, such as cytokines, nutritional status, and mechanical stress [198] .…”
Section: Nanomedicines For Stem Cell Therapymentioning
confidence: 99%
“…In a heart repair experiment, Lee et al [ 119 ] found that the NVs of MSCs derived from IONPs (IONP NVs) contain more heart repair therapeutic molecules (RNA and proteins) than normal MSC-derived NVs, which are mediated by the intracellular signal transduction modification triggered by the incorporation and ionization of iron oxide. With the slow ionization and assimilation of IONPs in vivo [ 120 ], the treatment of MSCs by IONP can improve the expression of anti-inflammatory and tissue repair cytokines by activating the JNK signal pathway [ 119 , 121 , 122 ]. At the same time, the level of therapeutic molecules in the prepared magnetic EVs increased.…”
Section: Effect Of Ionps On Evsmentioning
confidence: 99%